Compensatory responses of leaf physiology reduce effects of spring frost defoliation on temperate forest tree carbon uptake - Reinmann, Andrew B.; Bowers, Justin T.; Kaur, Prableen; Kohler, Clare (Frontiers in Forests and Global Change, 2023)
Spring frosts can defoliate trees, reduce canopy carbon assimilation, and alter interspecific competition dynamics. These events may become more common with climate change, but our understanding of the associated ecological impacts is limited by the stochastic nature of their occurrences. In 2020, a late spring frost defoliated oak (Quercus sp.), but not co-occurring maples (Acer sp.) across temperate broadleaf forests of the Hudson Highlands in southern New York State, U.S.A. Defoliation impacted 60% of this region’s forests and delayed full leaf expansion of oaks by 17 days. We used this event as an opportunity to advance understanding of how leaf-level physiology, radial growth, and interspecific competition dynamics of mature trees respond to frost-induced defoliation. We quantified leaf-level photosynthetic capacity, stomatal conductance, and water use efficiency, as well as basal area increment of defoliated red oak (Q. rubra) trees and non-defoliated red maple (A. rubrum) trees in 2020 (‘defoliation year’) and 2021 (‘reference year’). Oak defoliation provided red maple trees with a competitive edge in terms of photosynthetic capacity early in the growing season. However, the second cohort of red oak leaves that developed following defoliation had photosynthetic capacities that were 3-4 times higher than red maple trees by the second half of the growing season, likely facilitated by higher rates of stomatal conductance. The growing season mean photosynthetic capacities for the defoliation year were significantly higher for red oaks than red maples. Red oak basal area increment tended to be higher than red maple during both the defoliation and reference years. For both species basal area increment was significantly higher during the reference year than defoliation year, but the reasons remain unclear. Taken together, these findings demonstrate that temporal patterns of photosynthesis in temperate broadleaf forests are altered by defoliation events, but enhanced photosynthetic capacities of second cohort leaves can reduce the negative effects of delayed leaf expansion and mitigate competitive advantages conferred to undefoliated co-occurring tree species. We suggest that understanding a tree species’ ability to compensate for frost-induced defoliation is essential to accurately predict effects of extreme climate events on tree competition dynamics and ecosystem processes.